2017
DOI: 10.18632/oncotarget.22183
|View full text |Cite
|
Sign up to set email alerts
|

MiR-29b/TET1/ZEB2 signaling axis regulates metastatic properties and epithelial-mesenchymal transition in breast cancer cells

Abstract: MiR-29b has been reported to be both a suppressor and a promoter in breast cancer (BC) cells proliferation and metastasis. Significant efforts have been made to explain the seemingly contradictory effects of miR-29b on BC, but no answer has yet been clearly verified. In this study, we overexpressed and knocked down miR-29b in BC cell lines, modulated expression of its downstream target gene TET1 and downregulated a downstream target gene of TET1, ZEB2, to explore the regulatory mechanism of miR-29b in BC cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 56 publications
0
36
0
Order By: Relevance
“…Furthermore, it has been found that TET1 bound to the promoter of ZEB2 and inhibited cancer cell proliferation, colony formation and invasion ( Fig. 7) [35].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, it has been found that TET1 bound to the promoter of ZEB2 and inhibited cancer cell proliferation, colony formation and invasion ( Fig. 7) [35].…”
Section: Discussionmentioning
confidence: 92%
“…41 In addition, He et al reported that ZEB2 could form functional protein complexes with CdGAP in a GAP-independent manner and then regulate E-cadherin expression, thereby promoting the proliferation and metastasis of BC cells. 42 Both miR-204/ZEB2 axis 43 and miR-29b/TET1/ZEB2 axis 44 were involved in EMT and malignant evolution of BC cells. Zou et al showed that FAT10 could bind to ZEB2 directly, reducing its ubiquitination and enhancing its protein stability in BC cells, which contributed to the progress of BC.…”
Section: Discussionmentioning
confidence: 99%
“…The MiR‐371 family can be used as the plasma biomarkers for monitoring undifferentiated and potentially malignant human pluripotent stem cells (Salvatori et al, ). Besides, some groups have reported that miR‐29b‐3p plays important roles in cell apoptosis, inflammation, and oxidative stress (Jing et al, ; H. Wang et al, ; Xing et al, ; Zhang et al, ). MiR‐29 can be used as a clinical marker of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that miR‐29b plays important roles in a variety of diseases (Langsch et al, ; S. Zhou et al, ). This miRNA can prevent doxorubicin‐induced myocardial apoptosis by targeting BAX (Jing, Yang, Jiang, Chen, & Wang, ), inhibit high‐mobility group box 1/TLR4 signallling in liver fibrosis (Zhang et al, ), inhibit breast cancer via targeting the DNA modifying enzyme TET1 (H. Wang et al, ), and alleviate IgAN pathogenesis via targeting the cyclin‐dependent kinase 6 (Xing et al, ). However, there are no reports of the effects of miR‐29b‐3p on II/R injury.…”
Section: Introductionmentioning
confidence: 99%